Cholangiocarcinoma in an American Rhea (Rhea Americana araneipes) - Rocha, Paulo Ricardo Dell'armelina [UNESP] (2015)
Cholangiocarcinomas are neoplasms that originate from the bile duct epithelium. The present case described a cholangiocarcinoma in an adult female American Rhea (Rhea Americana araneipes) by means of gross, histopathology and immunohistochemistry. Irregular, firm, multifocal, yellow-white masses, measuring from 0.4 to 6cm in diameter were observed in both liver lobes. At the cut surface, multiple firm nodules filled with connective tissue were present. Microscopically, the neoplasia was composed of small, irregular, gland-like structures of neoplastic cells surrounded by connective tissue. The cells resembled epithelial cells of the hepatic biliary ducts. Neoplastic cells were positive for cytokeratin and negative for vimentin. This is the first report of a malignant fatal neoplasia in an American Rhea.